Numerical and experimental investigations of pressure fluctuations in single-channel pumps. (June 2018) - Tan, Linwei; Shi, Weidong; Zhang, Desheng; Zhou, Ling; Wang, Chuan
To elucidate the characteristics and generation mechanism of pressure fluctuations in single-channel pumps, the unsteady flow in three single-channel pumps with the same impeller equipped with a spiral volute (model 1), a circular volute (model 2), and a torus (model 3) were analyzed by computational fluid dynamics. Experiments on global performance characteristics in the volute of model 1 were performed, and fast response pressure sensors were installed in the spiral volute to measure pressure fluctuations. The results indicate that the numerical results are in good agreement with the experimental results. This study shows that a phase delay exists between different volute monitoring points and the pressure fluctuations in the volute are mainly caused by the potential interactions between the impeller blade and volute wall. Comparison of the pressure fluctuations amplitude of the impeller outlet shows that pressure fluctuation amplitude of model 3 is one order of magnitude lower than those of the others and the wake at the impeller outlet played an important role in pressure fluctuations. The standard deviation of pressure was introduced to describe the pressure fluctuations strength. It shows that the pressure fluctuation strength of the pressure surface is apparently higher than that of the suction surface, and the maximum pressure fluctuation strength in the blade is consistent with the flow separation area, indicating that flow separation is also an important factor for pressure fluctuations in single-channel pumps.